Breast Cancer Care in India: The Current Scenario and the Challenges for the Future - Agarwal, Gaurav (S. Karger GmbH, 2008)
The incidence of breast cancer is low in India, but rising. Breast cancer is the commonest cancer of urban Indian women and the second commonest in the rural women. Owing to the lack of awareness of this disease and in absence of a breast cancer screening program, the majority of breast cancers are diagnosed at a relatively advanced stage. The quality of care available for breast cancer patients varies widely according to where the patient is treated. Although there are some centers of excellence providing multimodality protocol-based treatment at par with the best anywhere in the world, the vast majority of breast cancer patients undergo inadequate and inappropriate treatment due to lack of high-quality infrastructure and sometimes skills, and above all financial resources. The recent emphasis on health education, early diagnosis of cancers, and more public facilities for cancer treatment are expected to bring about the much needed improvement in breast cancer care in India.